Self-Acceptance In Tiktok's "How I Love Being a Woman" Trend : An Audience Reception Research - Nazhifa Aqila Zahra (LITERA KULTURA : Journal of Literary and Cultural Studies, 2025)
This research explores how the TikTok trend “How I Love Being A Woman” represents self-acceptance among young women. Gaining significant popularity between 2023 and 2024, the trend showing women embrace and celebrate their identity as females. The study focuses on four highly popular videos from the trend selected based on high numbers of views, likes, and comments to analyze how self-acceptance is expressed through their content. This research is grounded in cultural studies and applies Stuart Hall’s theory of representation, combined with Albert Ellis’s REBT (Rational Emotive Behavior Therapy) theory, and examines audience interpretation using Hall’s audience reception theory. The findings highlight three key forms of self-acceptance displayed in the videos which are, acceptance of being a woman, acceptance of physical appearance and acceptance of domestic role. In terms of audience reception, some viewers take a negotiated or oppositional position toward the idea of acceptance of being a woman arguing that the expressions shown do not truly reflect self-acceptance. Meanwhile, audiences largely adopt a dominant position when it comes to acceptance of physical appearance and domestic roles. Overall, the majority of the audience aligns with the dominant reading of the trend.